DESIGN AND DEVELOPMENT OF WEB-BASED INFORMATION SYSTEM FOR OFFICE STATIONERY PROCUREMENT MANAGEMENT - Ginting, Novita BR; Afrianto, Yuggo; Wahyudi, Eko; Ningrum, Leny Tritanto; Jaenudin, Jejen (Jurnal Pilar Nusa Mandiri, 2022)
Office Stationery (ATK) is an item used to do written work such as paper, books, ink, pencils, pens, paper clamps, and others. ATK is a supporting tool that has an important role in implementing the administrative function of a company or agency. The management of ATK procurement in the Bogor Agricultural Institute (IPB) is under the coordination of the Directorate of Infrastructure, Facilities, and Campus Environmental Security (DPSPLK) as a coordination unit at the central level. So far, the procurement of ATK in every work unit in the IPB environment uses a direct purchase method. Direct purchasing methods cause problems and weaknesses, including: (1) price differences between providers for the same goods, (2) the quality of providers varies because each work unit directly selects providers, (3) vulnerability to price manipulation, (4) needed storage space for goods in each unit, (5) management and organization of ATK data are carried out partially in each work unit. Atk data management and organization have not been systemized, making it difficult for DPSPLK to reconcile data. An umbrella contract procurement method (framework contract) is applied to deal with problems in the direct purchase method. Management and organization of unsystematic ATK data, an integrated information system is built to facilitate DPSPLK reconciling data for reporting needs. The information system development method uses the waterfall method and testing using the User Acceptance Test (UAT) black-box type. This research resulted in the procurement and management application of ATK used by DPSPLK